Soft on errors? : the correcting mechanism of a Skolt Sami speller - Trosterud, Trond; Moshagen, Sjur (2021)
The article discusses correcting of typos due to erroneous use of the so-called soft sign in Skolt Sami, one of the most common orthographic symbols, and the most common source of typographic errors. The discussion is based upon the suggestion mechanism of an existing open source Skolt Sami speller. The discussion shows that with an improved suggestion mechanism, the speller is able to restore a single soft sign error in over 97 % of the cases, and remove a hypercorrect soft sign as first correction in 90 % of the cases. Allowing the target form to be within top-5, the correction performance is well above 99 %. Improving the suggestion mechanism also had a positive impact of its overall performance, rising the percentage of target forms within top-5 from 74.1 % to 84.7 %.